1987
DOI: 10.1007/bf00750730
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary mitochondrial hypertrophic cardiomyopathy with mitochondrial myopathy of skeletal muscle, congenital cataract and lactic acidosis

Abstract: A six day old boy died from an hereditary hypertrophic cardiomyopathy which was associated with mitochondrial myopathy of skeletal muscle, congenital cataract and lactic acidosis. In heart and skeletal muscle identical mitochondrial abnormalities were found: paucity and abnormal arrangement of cristae, formation and extrusion of vesicle-like structures and crystalline inclusions in the matrix compartment. Electron-cytochemistry revealed that only part of the mitochondria reacted positively for cytochrome oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…3,10 A morphometric study of myocardium in a patient with mitochondrial myopathy and HCM showed that the LVH was mainly due to cellular hypertrophy, which was attributed to increased mitochondrial mass. 11 Therefore, mitochondrial metabolic alterations due to the 3243 mutation would cause a compensatory increase in cardiac mitochondria, which leads to LVH.…”
Section: Discussionmentioning
confidence: 99%
“…3,10 A morphometric study of myocardium in a patient with mitochondrial myopathy and HCM showed that the LVH was mainly due to cellular hypertrophy, which was attributed to increased mitochondrial mass. 11 Therefore, mitochondrial metabolic alterations due to the 3243 mutation would cause a compensatory increase in cardiac mitochondria, which leads to LVH.…”
Section: Discussionmentioning
confidence: 99%
“…Hospital files from the patients mentioned in literature [1,3,6,7,8,10] were studied. Clinical data are summarised in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative ultrastructural data were derived by morphometric analysis according to the rules of Weibel [11]. Methods of morphometric analysis are described elsewhere [10]. We estimated the volume density (Vv) of subsarcolemmal mitochondria (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of mitochondrial encephalomyopathy and cataract has been frequently reported in congenital cases (15)(16)(17)(18)(19)(20), but it has also been reported in an adult case (21 …”
Section: F I G U R E 6 T H E L E F T S I D E O F T H E F I G U R E mentioning
confidence: 99%